Tolerability and outcome of palliative treatment for metastatic pulmonary carcinoma in cats. (4th October 2021) - Treggiari, E.; Pellin, M. A.; Valenti, P.; Curran, K. M.; Borrego, J. F.; Romanelli, G.; Mason, S. L.; Taylor, A.
Abstract : Objectives: Pulmonary carcinoma is uncommon in cats and reporting of outcomes following medical treatment is limited, especially in presence of metastases. The aim of this study was to describe the outcome of cats affected by metastatic primary pulmonary carcinoma and to evaluate the tolerability of palliative treatment in this patient population. Materials and Methods: Medical records were searched for cats with a cytological or histopathological diagnosis of primary pulmonary carcinoma and evidence of metastatic disease. Cats were treated with antineoplastic agents, corticosteroids, non‐steroidal anti‐inflammatory drugs (NSAIDs) or received no systemic treatment. Cases in which thoracic CT was not performed, and those lacking definitive diagnosis by cytology or histopathology or receiving curative‐intent surgery were excluded. Results: Thirty‐four cats were identified: 18 were treated with antineoplastic agents and 16 received corticosteroids, NSAIDs or no treatment. Presenting clinical signs included coughing (53%), tachypnoea (26%), gastrointestinal signs (35%) and lethargy (18%). CT scan identified metastases to the lung parenchyma in all cases and additional metastatic lesions in 10 of 34 (59%) cases; pleural effusion was detected in 11 cases (32%). The overall median survival time for all cats was 64 days [range 1‐1352 days; 95% confidence interval (CI) 48‐164]. Presence of respiratory signs at presentation was the only factor influencing survival in the multivariable analysis. Clinical significance: Medical treatment was well tolerated and appeared to palliate clinical signs in cats with metastatic pulmonary carcinoma, albeit with a modest duration and short overall survival. The role and benefit of chemotherapy/antineoplastic agents versus conventional palliative drugs in this setting remains unclear.